Reversible computing and implicit computational complexity - Kristiansen, Lars (Science of computer programming, 2022)
•We argue that there is a link between implicit computational complexity theory and reversible computation.•We introduce inherently reversible programming languages which capture the complexity classes etime and p.•Furthermore, we discuss and analyze higher-order versions of our reversible programming languages. We argue that there is a link between implicit computational complexity theory and reversible computation. We introduce inherently reversible programming languages which capture the complexity classes etime and ▪. Furthermore, we discuss and analyze higher-order versions of our reversible programming languages.